Prevalence of active transportation among adults in Latin America and the Caribbean: A systematic review of population-based studies - de Sá, Thiago Hérick; de Rezende, Leandro Fórnias Machado; Borges, Maria Carolina; Nakamura, Priscila Missaki [UNESP]; Anapolsky, Sebastian; Parra, Diana; Adami, Fernando; Monteiro, Carlos Augusto (Pan American Health Organization, 2017)
Objective. To describe the prevalence of “active” (self-propelled, human-powered) transportation in the Latin America and Caribbean (LAC) region over the past decade. Methods. MEDLINE, Excerpta Medica (Embase), SportDiscus, Lilacs, MediCarib, Web of Science, OVID, CINAHL, Scopus, Google Scholar, National Transportation Library, and TRIS/TRID were searched for articles on active transportation published between January 2003 and December 2014 with (at least) a title and abstract in English, Portuguese, or Spanish. Research was included in the study if the two reviewing authors agreed it 1) was conducted in an adult sample (≥ 18 years old), 2) was designed to be representative of any LAC area, and 3) reported at least one measure of active transportation. Reference lists of included papers and retrieved reviews were also checked. A total of 129 key informants (87 scientific experts and 42 government authorities) were contacted to identify additional candidate publications. Two other authors extracted the data independently. Results. A total of 10 459 unique records were found; the full texts of 143 were reviewed; and a total of 45 studies were included in the study, yielding estimates for 72 LAC settings, most of which were in Argentina, Brazil, and Colombia. No eligible studies were found for the years 2003-2004, resulting in a 10-year study time frame. Estimates were available for walking, cycling, or the combination of both, with a high degree of heterogeneity (heterogeneity index (I2) ≥ 99%). The median prevalence of active transportation (combining walking and cycling) was 12.0%, ranging from 5.1% (in Palmas, Brazil) to 58.9% (in Rio Claro, Brazil). Men cycled more than women in all regions for which information was available. The opposite was true for walking. Conclusions. Prevalence of active transportation in LAC varied widely, with great heterogeneity and uneven distribution of studies across countries, indicating the need for efforts to build comprehensive surveillance systems with standardized, timely, and detailed estimates of active transportation in order to support policy planning and evaluation.
Prevalencia del transporte activo en los adultos de América Latina y el Caribe: Revisión sistemática de estudios poblacionales
Prevalência do deslocamento ativo em adultos na América Latina e Caribe: Revisão sistemática de estudos populacionais
Keywords: Argentina; Brazil; Caribbean Region; Colombia; Healthy city; Latin America; Motor vehicles; Transportation; Urban health; Walking